2022
DOI: 10.1155/2022/4849758
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Methylene Blue Dye Using Biowaste Materials: Barley Bran and Enset Midrib Leaf

Abstract: In this study, several biowaste materials are screened for adsorptive removal of methylene blue (MB) from synthetic water. Among the tested adsorbents, barley (Hordeum vulgare) bran (BB) and enset (Ensete ventricosum midrib leaf, EVML) were selected for further evaluation of MB (a model cationic dye) adsorption. Batch MB adsorption performance of BB and EVML adsorbents was significantly high in a wide pH range (4-9). The well fitting of experimental data with pseudosecond-order kinetic model suggests a monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Common adsorbents like activated carbon can be costly; therefore, researchers are exploring alternative, low cost renewable materials sourced from various waste streams to address this pressing environmental issue. 5 This study reported the use of two such waste products for the synthesis of a novel adsorbent for wastewater treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common adsorbents like activated carbon can be costly; therefore, researchers are exploring alternative, low cost renewable materials sourced from various waste streams to address this pressing environmental issue. 5 This study reported the use of two such waste products for the synthesis of a novel adsorbent for wastewater treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While untreated industrial effluents, particularly from textile industries, introduce complex and recalcitrant pollutants (such as synthetic dyes) into the aquatic environment, adsorption offers a promising solution to remove such persistent pollutants. Common adsorbents like activated carbon can be costly; therefore, researchers are exploring alternative, low cost renewable materials sourced from various waste streams to address this pressing environmental issue …”
Section: Introductionmentioning
confidence: 99%
“…To reduce the global burden of diseases, it is essential to implement appropriate treatment methods before water consumption. Based on the advantages and disadvantages of different methods tested to treat water, adsorption, particularly on activated carbons (ACs), has been highlighted [6][7][8][9][10]. The ease of use, low implementation costs, potential for multiple reuse of the adsorbent materials, and the recuperation of the adsorbate are the main benefits of the adsorption process [11].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents some findings related to using natural adsorbents, without any treatment, in eliminating MB from the aqueous phase. Enset midrib leaf 35.5 5.66 1 [9] Sugarcane bagasse 9.4 24 [18] Chlorella vulgaris microalgae 275 --72 [20] Corn husk 30.3 6.2 0.25 [21] Ficus carica bast treated with H 2 SO 4 55.56 7.8 1.33 [22] Natural adsorbents (review) ------ [12,13] Potato peel 48.7 --1.0 [23] Date palm leaves 43.1 6.5 2.7 [16] Modified zeolites 133.1 [24] Hylocereus undatus (dragon fruit peels) 192.31 5.6 0.15-2 [25] MB has become increasingly important in the field of water treatment because it is environmentally persistent, toxic, carcinogenic, and mutagenic [26][27][28][29][30][31][32][33][34][35][36]. These effects are quite similar to the side effects caused by the majority of organic pollutants present in water used for household activities by rural populations in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several low cost biosorbents such as tea waste, fava bean peel [9], rice husk [19], banana fibre [20], coconut fibre [20], sawdust [20], barley bran [21], enset midrib leaf [21], eucalyptus sheathina bark [22], solanum tuberosum [23], pisum sativum peels [23] and rice straw [24] have been reported in literature for the removal of dyes. However, to the best of our knowledge the use of kocho for the remediation of methylene blue (cationic model dye) present in wastewater has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%